The Pattern of Education on Aqidah, Worship, The morals of the Santri Tassbeh Baitul Qur'an Islamic Boarding School, Pinrang Regency - Muh. Nur Fajri. R; Muhammad Saleh; Muh. Akib D; Hannani; Marhani (International Journal of Health, Economics, and Social Sciences (IJHESS), 2024)
The problem in this study is that the students do not understand the education of Aqidah, worship, and morals towards themselves. This thesis aims to describe the pattern of education in providing understanding of Aqidah, increasing worship, and forming morals through fostering students in carrying out learning programs at the Tassbeh Baitul Quran Islamic Boarding School, Pinrang Regency. The type of research used is descriptive qualitative research. The approach taken is phenomenology. The data sources of this research are primary and secondary data sources. Methods of data collection by observation, interviews and documentation. Data analysis techniques with non-statistical analysis, namely by collecting, reducing, presenting and drawing conclusions. Testing the validity of the data is by reference, participation and data triangulation. The results of this study are (1) the pattern of education in understanding the Aqidah of Santri at the Tassbeh Baitul Quran Islamic Boarding School, Pinrang Regency, which is carried out with an authoritarian system through the morning halaqah program and routine taklim. (2) Educational Patterns in Improving Santri Worship at the Tassbeh Baitul Quran Islamic Boarding School, Pinrang Regency, namely carried out with an authoritarian system and parenting through the dawn halaqah program, routine taklim, and absence of worship control. 3) The pattern of education in the formation of the morals of the Santri Tassbeh Baitul Quran Islamic Boarding School in Pinrang Regency is carried out with a system of upbringing and character building through a program of implementing rules, special advice, calling parents. The first implication of this research is that future researchers can develop research on educational patterns applied in Islamic boarding schools. Secondly, this educational program can continue to be implemented in Islamic boarding schools, but there is still a need to strengthen the communication between supervisors and parents in managing the program.